INCREASING THE EFFECTIVENESS OF NARCOTICS REHABILITATION: CHALLENGES AND STEPS OF BNN GORONTALO CITY - Igirisa, Siti Choirunnisa; Rachman, Ellys; Gobel, Lisda Van (Universitas Negeri Gorontalo, 2023)
This study aims to determine the inhibiting factors of the effectiveness of social rehabilitation by the National Narcotics Agency (BNN) Gorontalo City. The type of research used is Descriptive using a qualitative approach method, which refers to three Focus indicators, namely, Policy, Awareness of Former Users and Socialization. Research results show that: The social rehabilitation program carried out by the National Narcotics Agency of Gorontalo City has not been optimal. This is due to weak policies or programs related to social rehabilitation procedures during the Covid-19 pandemic, forcing patients to be unable to conduct direct counseling with BNN Gorontalo City Counselors, Lack of Awareness Level by Former Users in participating in social rehabilitation which has an impact on the patient's health level declining, and Lack of Maximum Socialization carried out by counselors to patients which has an impact on weak control over patients Social rehabilitation. Through this research, it is recommended to implementors to be able to further optimize the implementation of this rehabilitation program so that in the future the level of awareness of former drug users will increase. So that what is the goal to be free from narcotics is realized.